The social base and career development of Spanish mayors - Navarro, Carmen; Sanz, Alberto (Asociacion Espanola de Ciencia Politica y de la Administracion, 2018)
The growing corpus of studies about political elites in Spain has tended to focus on national and regional parliaments and executives,rather than on the municipal level of government. And yet,it is in these local settings that politicians acquire skills and political experience,develop their notions of democracy,and often start their political careers. Exploring patterns of political recruitment in Spanish local democracies allows us to look at some of the literature findings on this topic and check whether they also apply at the municipal level in Spain,enhancing in this way our understanding of who governs our cities,too. This article analyzes Spanish mayors' social profiles,their patterns of professionalization and their political ambitions,trying to address questions such as: do municipal leaders share a common background? Are they amateurs or professionals in politics? Is the municipal level the first stage of an identifiable political career of Spanish representatives? In responding to these questions,this paper draws on survey data from a representative sample of 303 mayors in municipalities with populations larger than 10 000 inhabitants. The analysis confirms that Spanish mayors follow to a great extent the patterns found in studies of political elites and particularly those of local executives in other countries in Europe,but with some distinctive singularities. © Revista Española de Ciencia Política,2018.
Keywords: Local democracy; Local government; Mayors; Political leaders; Political recruitment; Spain; 59 Ciencia Política::5904 Instituciones políticas; ODS 4 - Educación de calidad; ODS 10 - Reducción de las desigualdades